Poor prognosis factors in SLE: results of 5-year follow-up - E A Sushchuk; A B Zborovskiy; E A Suschuk; A B Zborovsky (Терапевтический архив, 2009)
Aim. To determine factors of poor prognosis of systemic lupus erythematosus (SLE). Material and methods. Clinical and device examinations were made in 64 patients hospitalized with verified SLE. Its activity was assessed by SLAM and SLEDAI indices, severity - with SLICC/ACR. Five years after the primary examination the patients were re-examined. Prognostic factors were investigated using multiple linear regression and binary logistic regression. Results. A 5-year survival of SLE patients was 87.5%. For 5 years SLICC/ACR has risen from 1.24 ± 1.29 to 2.58 ± 1.89 points (p < 0.001). Reproductive, nervous, cardiovascular and osseomuscular disorders made the greatest contribution to this rise. The age of SLE onset, SLICC/ACR at the start of the study, the absence of a rapid response to treatment were significant predictors of SLICC/ACR rise in the model of linear regression. This model explains 62.7% of the dependent index variance. The model of binary logistic regression, in which a dependent variable was survival, identified the same three indices as statistically significant. The model explained 74.4% of 5-year survival variance and predicted an outcome correctly in 86.2% cases. Conclusion. Key factors of a poor SLE prognosis are a late SLE onset, a severe initial lesion and no rapid response to therapy.